2011
DOI: 10.1007/s00228-011-1131-3
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between CAG repeat polymorphism in the androgen receptor gene and the outcome of rheumatoid arthritis treatment with leflunomide

Abstract: PurposeLeflunomide (LEF) is a disease-modifying antirheumatic drug used for treating rheumatoid arthritis (RA) and the action of which may be modified by sex hormones. The aim of this study was to examine the association between CAG repeat polymorphism in the androgen receptor (AR) gene and the response to treatment with LEF in women with RA.MethodsWe studied 114 women diagnosed with RA and treated with LEF (20 mg daily). Follow-up was 12 months. CAG repeat polymorphism was determined using polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…e study was approved by the ethics committee of the Medicine College of Inner Mongolia University for the Nationalities (IMUNMCEC20210412 [1]). Male Wistar rats (200 ± 10 g) were provided by YiSi Laboratory Animal Technology Co., Ltd. (Changchun, China).…”
Section: Adjuvant-induced Arthritis Model Establishment Andmentioning
confidence: 99%
See 1 more Smart Citation
“…e study was approved by the ethics committee of the Medicine College of Inner Mongolia University for the Nationalities (IMUNMCEC20210412 [1]). Male Wistar rats (200 ± 10 g) were provided by YiSi Laboratory Animal Technology Co., Ltd. (Changchun, China).…”
Section: Adjuvant-induced Arthritis Model Establishment Andmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a common systemic autoimmune disease characterized by symmetric polyarthritis and joint destruction [1]. It is traditionally treated with methotrexate combined with the botanical preparation of Tripterygium wilfordii.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that 17b-estradiol and testosterone respectively seem to contrast and to synergize the LEF downregulatory activity [ 110 ]. In another study, Dziedziejko et al [ 111 ] examined the association between CAG repeat polymorphism in the androgen receptor (AR) gene and response to therapy in women with RA treated with LEF. The AR gene, present on the X chromosome, contains a highly polymorphic CAG (glutamine) repeat in the region encoding NH2-terminal transactivation domain, which normally varies between 9 and 37 repeats (approximately 10–30 in Caucasians) [ 112 , 113 ].…”
Section: Pharmacogenetic Biomarkersmentioning
confidence: 99%
“…The authors studied 114 women diagnosed with RA and treated with LEF 20 mg daily, with a 12-month follow-up. No statistically significant associations between CAG repeat polymorphism in the AR gene and improvement of disease activity parameters was found, suggesting no correlation between CAG repeat polymorphism in the AR gene and response to treatment with LEF in women with RA [ 111 ].…”
Section: Pharmacogenetic Biomarkersmentioning
confidence: 99%